Anaerobic digestion of calotropis procera for biogas production in arid and semi-arid regions: A case study of Chad. Issue 1 (31st December 2022) - Djimtoingar, Stephanie Solal; Derkyi, Nana Sarfo Agyemang; Kuranchie, Francis Atta; Sarquah, Khadija
Abstract: Chad is among the many African countries having the most electrification problems (8.8% access in 2019) relating to the country's poor economy and dependency on fossil fuels. On the other hand, the utilization of biomass for energy needs has been proven successful in various economies. Calotropis Procera, a bush latex plant wildly known for its multiple merits, is abundant in Chad, with an annual average of 6.3 tons per hectare on a wet basis. However, these are considered nuisance and resources are invested in getting rid of them. This study presents the first attempt to assess the biogas potential and prospects from Calotropis Procera for energy production in Chad. Theoretical estimations, field visits and experimental approaches were employed in this study. The experimental results were favourable as it was found that the stem of the plant achieved a biogas yield of 17, 744 ± 12 mL and a biomethane production of 1.439 ± 0.31 L/g.VS while its leaves produced 8500 ± 4 mL of biogas for 0.4409 ± 0.15 L/g.VS of Biomethane. Estimations showed that the average annual availability of 6.3 tons of Calotropis Procera in Chad could produce 891.61 m 3 and 9150.884 m 3 of biogas from the leaves and stem, respectively. The theoretical energy potential of the Calotropis Procera leaves was estimated at 4.0861 MWh/yr and that of the Calotropis Procera stem at 13.104 MWh/yr. The findings from this study are useful to complement efforts in finding sustainable energy alternatives and resources in Chad and similar contexts. Also, this gives a technical basis for further research in economic and environmental sustainability as well as for policymakers on the production of energy from Calotropis Procera towards significant gains.